PEMAHAMAN SISWA TENTANG MANAJEMEN KARIR PASCA LAYANAN INFORMASI KARIR DI MAN 2 BATUSANGKAR - Wahyuni, Roza Sri; Yuliani, Tri (UIN Imam Bonjol Padang, 2020)
This study aims to determine students' understanding of career selection after obtaining information services including career selection on sub-variables of motivation, knowledge, personality, abilities. One of the uses of the results of this study is as information for students, lecturers, teachers, students, and readers on how students' understanding of career selection in MAN 2 Batusangkar. The research method used in this study is the method of